Exploring the gradient: The economic benefits of 'nearby' schools on rural communities. (May 2019) - Sipple, John W.; Francis, Joe D.; Fiduccia, Peter Cody
Abstract: Little is known about the socioeconomic impacts of the presence or absence of schools on local communities. In other words, are communities better off with or without a local school in or near its community center? In one of the few studies on this, Lyson (2002) argued that the presence of schools provides significant social and economic benefits to rural communities including higher property values and incomes. The main goal if this paper is to interrogate the area outside villages – what we measure as a 5 mile gradient or boundary. The data for this study are drawn from US Census TIGER files, American Community Survey data, and the NY State Department of Education including public school finance, demographic, enrollment, and performance data. In short, we are modeling the gradient around villages to see if village economic indicators vary with the concentration of public schools and the distance schools are from the center of the village. We find strong support for the assumption that schools are important to the economic vitality of rural communities and support for our method of geo-locating community institutions and measuring distance and concentration - what we term School proximity Index (SPI). We find that housing values, per-capita income, and household income significantly and positively vary with our SPI above and beyond the effects of age-structure, proportion of households with children, proportion of population that is white, self-employment rates. It is important to note, however, that the causal direction of these effects remains uncertain. While the relationship is indeed positive, whether the presence of a school promotes enhance community vitality or enhance community vitality promotes the presence of a school must be further examined. Highlights: Explores the relationship between school location/concentration and village economic vitality Develops a School Proximity Indicator (SPI) by generating a 5 mile gradient around 309 villages in NYS using GIS analysis. The SPI is a function of both distance from village center to school but also of the number of schools (at variable distances). We find strong and consistent relationship between the SPI and local village economic conditions (income and house value). Beyond SPI, we find a significant negative finding between the increasing proportion of white residents and the economic indicators.